Childfree in the Perspective of Islamic Feminism: A Comparative Study of the Thoughts of K.H. Husein Muhammad, Amina Wadud, and Fatima Mernissi - Moch Aufal Hadliq Khaiyyul Millati Waddin; Naser Ali Abdulghani (Perkumpulan Dosen Tarbiyah Islam, Indonesia, 2025)
The childfree phenomenon among contemporary Muslims has sparked theological and social debate, highlighting the tension between the normative construction of motherhood in Islam and women's growing awareness of their bodily authority and social roles. This study aims to analyze and compare the responses of three Islamic feminist figures, K.H. Husein Muhammad, Amina Wadud, and Fatima Mernissi, to the childfree issue. The method used is a qualitative approach through literature study and comparative-critical discourse analysis. The results show that although their approaches differ, namely maqāṣidiyah (Husein Muhammad), textual hermeneutics (Amina Wadud), and historical-sociological criticism (Fatima Mernissi), all recognize women's right to autonomy over their bodies and reproductive decisions. Husein Muhammad emphasizes the aspect of maslahah within the framework of sharia, Wadud highlights spiritual justice and mutual benefit, while Mernissi views the childfree phenomenon as a form of resistance to the patriarchal narrative of motherhood. This article contributes to broadening the horizons of contemporary Muslim women through a synthesis of women's, theological, and sociological approaches to the discourse on Muslim women's reproductive rights.